Myeloperoxidase Promoter Polymorphism −463G Is Associated With More Severe Clinical Expression of Cystic Fibrosis Pulmonary Disease - Wanda F. Reynolds; Isabelle Sermet-Gaudelus; Valérie Gausson; Marie-Noëlle Feuillet; Jean-Paul Bonnefont; Gérard Lenoir; Béatrice Descamps-Latscha; Véronique Witko-Sarsat (Mediators of Inflammation)
The severity of cystic fibrosis (CF) pulmonary disease is not directly related to CFTR genotype but depends upon several parameters, including neutrophil-dominated inflammation. Identification of agents modulating inflammation constitutes a relevant goal. Myeloperoxidase (MPO) is involved in both microbicidal and proinflammatory neutrophil activities. The aim of this study was to evaluate whether the −463GA MPO promoter polymorphism is linked to clinical severity of CF-associated pulmonary inflammation. This polymorphism significantly affects the level of MPO gene expression in leukocytes and the G allele is more expressing than the A allele. We show that MPO genotype significantly influences the severity of pulmonary disease in early stages, prior to the development of chronic lung infections, with GG genotype being associated with more severe CF disease. Our findings indicate that the level of MPO gene expression influences the CF pathogenesis, presumably reflecting cellular damage by MPO-generated oxidants or other activity of MPO in airway inflammation.